Allergenic invasive plant Ambrosia artemisiifolia L. in Poland: threat and selected aspects of biology - Tokarska-Guzik, Barbara; Bzdęga, Katarzyna; Koszela, Katarzyna; Żabińska, Izabela; Krzuś, Barbara; Sajan, Małgorzata; Sendek, Agnieszka (Biodiversity: Research and Conservation, 2011)
The study presents the current state of research on Ambrosia artemisiifolia in Poland within its wider scientific background and gives the results of some field and laboratory investigations. This annual plant is characterised by a high level of production of seeds, easily dispersed by different vectors. Ragweed pollen is a strong allergen considered to be one of the most dangerous pollen allergens in the world. Being a serious hazard to human health, it is also considered as an "environmental weed" causing economic threat. The main aim of the study is to verify the status of the species in the flora of Poland, to assess the threat and discuss possibilities to prevent its future spread.